1988
DOI: 10.1083/jcb.106.1.171
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in chondrocyte cytoskeletal architecture during phenotypic modulation by retinoic acid and dihydrocytochalasin B-induced reexpression.

Abstract: Abstract. The differentiated phenotype of rabbit articular chondrocytes was modulated in primary culture by treatment with 1 pg/ml retinoic acid (RA) and reexpressed in secondary culture by treatment with the microfilament-disruptive drug dihydrocytochalasin B (DHCB) in the absence of RA. Because the effective dose of DHCB (3 ~tM) did not elicit detectable cell rounding or retraction, the nature and extent of microfilament modification responsible for induction of reexpression was evaluated. The network of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
93
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(99 citation statements)
references
References 27 publications
6
93
0
Order By: Relevance
“…The lack of effect of sConA on cell shape suggests that the ConAinduced cell-shape change from fibroblastic cells to spherical Journal of Cell Science 116 (10) cells is not directly linked with the ConA-induced, aggrecan and type II collagen expressions. This conclusion was unexpected because the cell shape has a great effect on the differentiation of prechondrogenic cells and dedifferentiated cartilage cells in some experimental systems (Zanetti and Solursh, 1984;Brown and Benya, 1988). However, in cultures of MTf-overexpressing C3H10T1/2 cells, ConA altered cell shape but did not enhance the expression of aggrecan or type II collagen (data not shown), which also suggests that MTf has two distinct roles: modulating cell shape and stimulating chondrocyte phenotypic expression.…”
Section: Discussionmentioning
confidence: 60%
“…The lack of effect of sConA on cell shape suggests that the ConAinduced cell-shape change from fibroblastic cells to spherical Journal of Cell Science 116 (10) cells is not directly linked with the ConA-induced, aggrecan and type II collagen expressions. This conclusion was unexpected because the cell shape has a great effect on the differentiation of prechondrogenic cells and dedifferentiated cartilage cells in some experimental systems (Zanetti and Solursh, 1984;Brown and Benya, 1988). However, in cultures of MTf-overexpressing C3H10T1/2 cells, ConA altered cell shape but did not enhance the expression of aggrecan or type II collagen (data not shown), which also suggests that MTf has two distinct roles: modulating cell shape and stimulating chondrocyte phenotypic expression.…”
Section: Discussionmentioning
confidence: 60%
“…The cellular phenotype can be preserved when chondrocytes are cultured in 3-dimensional matrices such as agarose (7), alginate (8)(9)(10), or collagen gels (11). Other researchers have found that the metabolic and morphologic changes could be reversed by the disruption of the cytoskeletal complex (12,13). The metabolic activity of isolated chondrocytes may be modulated by the matrix around the cells (8,14,15).…”
mentioning
confidence: 98%
“…cDNA was prepared from 1 g total RNA using the Superscript First-Strand Synthesis System for RT-PCR (Invitrogen) with p(dT) [12][13][14][15][16][17][18] and random hexamer primers (Amersham Pharmacia Biotech, Piscataway, NJ, USA). PCR amplification was performed in a 50-l reaction volume containing 1 l cDNA reaction and using ampliTaq Gold polymerase (Perkin Elmer).…”
Section: Rna Isolation and Rt-pcrmentioning
confidence: 99%
“…(3,8) Chondrogenic gene expression is closely correlated to cell shape, (9,10) and the organization of the actin cytoskeleton plays an important function in the control of chondrogenic differentiation. (11)(12)(13)(14) Furthermore, mutations in the genes encoding the actinbinding proteins Filamin A and B have recently been identified as molecular causes of several human diseases characterized by severe skeletal defects. (15,16) All these data suggest that signaling pathways modulating actin organization could play crucial roles in the regulation of chondrocyte physiology.…”
mentioning
confidence: 99%